Pregnancy in CADASIL. (12th June 2017) - Donnini, I.; Rinnoci, V.; Nannucci, S.; Valenti, R.; Pescini, F.; Mariani, G.; Bianchi, S.; Dotti, M. T.; Federico, A.; Inzitari, D.; Pantoni, L.
Abstract : Objectives: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited cerebral small vessel disease caused by NOTCH3 gene mutations. CADASIL women are frequently considered at high risk of systemic vascular events during pregnancy and often prescribed with antithrombotic drugs. This decision is not evidence‐based considering the lack of data about pregnancy outcome in CADASIL. We describe our experience on pregnancy in CADASIL patients. Materials and methods: We reviewed records of 50 CADASIL females followed in our center, and we collected prospective information in six patients for a total of 93 pregnancies. Results: No woman had the disease onset or suffered from cerebral vascular ischemic events during pregnancy. Sixteen miscarriages (17.2%) were recorded. There were 72 vaginal births, and five cesarean sections. Considering the six patients followed prospectively (for a total of eight pregnancies), data on fetal growth and newborns weight were in line with those from the general population. Considering gestational complications, we recorded mild proteinuria without hypertension in one patient and hyperinsulinemia and pre‐eclampsia in another affected by a known nephropathy. Antithrombotic drugs were used in three patients, in one for an unrelated coexisting prothrombotic condition. Conclusions: CADASIL does not seem to be associated with an unfavorable outcome of pregnancy either for women and fetuses. Patients and treating physicians should be reassured that pregnancy can be safely initiated in CADASIL, as there is no evidence to support a specific preventive antithrombotic treatment during pregnancy in CADASIL. Larger studies are needed to definitively confirm these conclusions.